2022
DOI: 10.1371/journal.pone.0279557
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine knowledge, attitudes, and experiences of health care workers in Perth, Western Australia: A qualitative study

Abstract: Introduction Health care workers (HCWs) faced an increased risk of Coronavirus Disease 2019 (COVID-19). Australia’s COVID-19 vaccine rollout commenced in February 2021 to priority groups, including HCWs. Given their increased risk, as well as influence on patients’ vaccine uptake, it was important that HCWs had a positive COVID-19 vaccination experience, as well as trusting the vaccine safety and efficacy data. Methods Semi-structured interviews were undertaken with 19 public- and privately-practicing HCWs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The findings of this study were consistent with the existing international and inter‐state literature on this topic. The theme of operational barriers identified is mirrored in multiple other studies 20–22,31 . Turcu‐Stiolica et al, 22 a cross‐sectional study of 636 community pharmacies, identified operational barriers to vaccination including access to training and physical space for vaccinating clients and storing vaccinations.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The findings of this study were consistent with the existing international and inter‐state literature on this topic. The theme of operational barriers identified is mirrored in multiple other studies 20–22,31 . Turcu‐Stiolica et al, 22 a cross‐sectional study of 636 community pharmacies, identified operational barriers to vaccination including access to training and physical space for vaccinating clients and storing vaccinations.…”
Section: Discussionmentioning
confidence: 87%
“…Kauffman et al 12 suggested that websites and videos to refer patients to would be helpful. Carlson et al 31 interviewed HCWs working in private practice in Perth, Western Australia and suggested that the inclusion of more information on vaccine safety, efficacy, development process and normalising common side effects in public campaigns could ‘counteract sensationalist media’ and increase vaccine acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation